Evolution, Composition and Regulation of Supernumerary B Chromosomes - Martins, Cesar (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Supernumerary B chromosomes (Bs) are dispensable genetic elements found in thousands of species of plants and animals, and some fungi. Since their discovery more than a century ago, they have been a source of puzzlement, as they only occur in some members of a population and are absent from others. When they do occur, they are often harmful, and in the absence of "selfishness", based on mechanisms of mitotic and meiotic drive, there appears to be no obvious reason for their existence. Cytogeneticists have long wrestled with questions about the biological existence of these enigmatic elements, including their lack of any adaptive properties, apparent absence of functional genes, their origin, sequence organization, and co-evolution as nuclear parasites. Emerging new technologies are now enabling researchers to step up a gear, to look enthusiastically beyond the previous limits of the horizon, and to uncover the secrets of these "silent" chromosomes. This book provides a comprehensive guide to theoretical advancements in the field of B chromosome research in both animal and plant systems.